SMART SECURITY DEVELOPMENT TO REALIZE SECURITY AND PUBLIC ORDER IN THE CAPITAL CITY OF NUSANTARA - Satria Rizkiano; K.P. Suharyono S. Hadiningrat (JIPOWER : Journal of Intellectual Power, 2024)
The relocation of the National Capital City (IKN) from Jakarta to the archipelago in East Kalimantan province is carried out by the Government of the Republic of Indonesia based on Law Number 3 of 2022 concerning the National Capital City. Physical construction is currently underway and the first footprint of the Joko Widodo Administration was marked by the 79th Commemoration Ceremony of the Seconds of the Proclamation of Independence of the Republic of Indonesia. The opportunities and challenges are very dynamic so that a strong commitment from the next government is needed so that the development and relocation of the National Capital City takes place successfully in line with its goals and vision as: a) a sustainable city in the world; b) a future economic driver for Indonesia; and c) a symbol of national identity that represents the diversity of the Indonesian nation, based on Pancasila and the 1945 Constitution of the Republic of Indonesia. For this reason, safe and conducive conditions supported by all elements of nationality are needed; among others through the implementation of a smart security system. The research method used is a descriptive method to find and describe variables related to the development of smart security to realize public order in IKN Nusantara (Suharsimi, 2011). The tools used to analyze data are SWOT Analysis (Albert S. Humphrey). The approach used is a qualitative approach to describe the conceptual or discussion of variables in a narrative (non-numerical) manner. With these methods and approaches, this research is expected to have novelty, namely finding a smart security system to realize public order in IKN Nusantara. From the discussion, it is concluded that: a) The concept of Smart Security to be built at IKN Nusantara is policing that utilizes advances in information and communication technology; b) the factors analyzed are internal factors, namely Strengths and Weaknesses, while the external factors are opportunities and threats; c) the efforts made to build smart security use an aggressive strategy where strengths must be optimized to seize profitable opportunities. And the recommendations are addressed to : a) The IKN Nusantara Authority together with the Indonesian National Police to plan and build smart security that is integrated with smart cities in IKN Nusantara; and b) The IKN Nusantara Authority together with the Indonesian National Police establish a pentha-based collaboration in building smart security that is integrated with smart cities in the KN Nusantara.